4(x+6)=4(x+7)

Simple and best practice solution for 4(x+6)=4(x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+6)=4(x+7) equation:



4(x+6)=4(x+7)
We move all terms to the left:
4(x+6)-(4(x+7))=0
We multiply parentheses
4x-(4(x+7))+24=0
We calculate terms in parentheses: -(4(x+7)), so:
4(x+7)
We multiply parentheses
4x+28
Back to the equation:
-(4x+28)
We get rid of parentheses
4x-4x-28+24=0
We add all the numbers together, and all the variables
-4!=0
There is no solution for this equation

See similar equations:

| 8n-5=-19(12+n) | | 8a+12=80 | | 10x-8=20-14x | | V=1/3πr^2 | | 6f=-66 | | 5(x+5)=5x-1 | | 5n+-4n=5 | | -12+2x=-14 | | 5-x-x=- | | 3v-42=5(v-6) | | 2n-13=-19(16+4n) | | a/9=1/23 | | 289=69-u | | 2(x-2)=5x-16 | | -30=12-6x | | 5/8=3/y | | 6x+12+7x=-4 | | -2(x^2-7)^2+3=-47 | | 4(k+9)=4(k+9) | | −4−0.2x+11=−0.8x+10 | | 5x−7=58 | | ​−4−0.2x+11=−0.8x+10 | | 5x−2=3x+1 | | 12=0.005x | | 116(x−40)=5+x | | 11-3a+6=27 | | 5(x−2)=3x+1 | | 6(x+6)=6x+4 | | −5(3x−15)=2(x−1)−59 | | 10h+4=11 | | 7b^2+3b+42=0 | | 3x-6+4x=18-x |

Equations solver categories